Low-Energy Plasma Focus Proves Medical Grade Radioactivity Production - Roshan, M.V; Sadeghi, H; Fazelpoor, S; Lee, S (IEEE, 2018)
The plasma focus (PF) emerged as a potential prospect to produce radionuclide, but the experimental data are not significant in favor of practical medical radioactivity. Empirical scaling grants a set of magnetic lens to enhance the nuclear activity. The experimental radioactivity of low-energy devices is in the range of kilobecquerel and rises to megabecquerel by optimizing and operating at a few hertz. Magnetically driven ion beam improves the radioactivity to the prescribed value of gigabecquerel for nuclear imaging …